The Aftermarket Liquidity of IPOS: Evidence from Software Industry - Razvan Ioan TATARU; Andreea IORDACHE; Catalina-Ioana TOADER (Communications of International Proceedings, 2025)
Given the growing interest in how behavioral factors could explain the dynamics of the financial markets, our paper explores a relatively under-researched area, the aftermarket liquidity of IPOs. Hence, our paper contributes to the existing literature by examining the driving factors of the aftermarket liquidity of the IPO, including behavioral variables such as investor optimism and pessimism. Our study focuses on the US companies from software industry over the period January 2006 – December 2020. Based on an OLS regression approach, we show that the state of the market impacts the aftermarket liquidity of the IPO. In particular, an optimistic state of the market increases the aftermarket liquidity of the IPO. Moreover, we confirm prior literature that documented that underpricing significantly influences aftermarket liquidity of the IPO. Therefore, we provide evidence in support of the theory that states the firms underprice their IPOs in order to obtain more liquidity. Our findings provide a better understanding of the determinants of the liquidity of IPOs, offering valuable insight for investors due to their implications in asset pricing. Our results are also important for policymakers and regulators since a higher liquidity could lead to economic growth in the long run.
Keywords: Initial Public Offerings; Liquidity; Investor sentiment; US stock markets